A case series describing the epidemiology and clinical characteristics of COVID-19 infection in Jilin Province. Issue 1 (1st January 2020) - Du, Na; Chen, Haiying; Zhang, Qing; Che, Lihe; Lou, Lixin; Li, Xiaohua; Zhang, Kaiyu; Bao, Wanguo
ABSTRACT: Since its outbreak in Wuhan, Hubei Province China, 2019-coronavirus infected disease (COVID-19) had been widely spread all over the world, the control of which calls for a better understanding of its epidemiology and clinical characteristics. We included 12 confirmed cases of COVID-19 in First Affiliated Hospital of Jilin University from 23 January 2020 to 11 February 2020, which were retrospectively analyzed for epidemiological, demographic, clinical, laboratory, and radiological features. All the patients were confirmed by nucleic acid detection, the average age of whom was 45.25 years (range, 23–79 years). Most patients had a history of Wuhan traveling or had contact with Wuhan travelers or infected cases. Obvious family cluster was observed. Clinical manifestations included fever (12/12), fatigue (10/12), cough (6/12), sore throat (4/12), headache (3/12), and diarrhea (2/12). Only three out of eight patients had pneumonia manifestation on radiography. Most patients had a normal white blood cell (WBC) count and normal or reduced lymphocyte (LY) count. Pneumonia changes were observed in all the four patients who underwent a chest CT scan. Only one elderly patient developed severe pneumonia, while all the rest were mild disease and had a self-limiting course.